Perancangan Sistem Informasi Jadwal Pertandingan Bola Basket Berbasis Web pada Perbasi Kabupaten Serang - Rimasya Ayu Jaeningsih; Selly Septiani; Ananda Saskira (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The development of information technology has significantly impacted various sectors of life, including sports. In Serang Regency, basketball is a popular sport and frequently hosts competitive tournaments. However, the management and publication of match schedules is still done manually. This manual process is considered ineffective because it takes longer, has the potential to lead to misinformation, and makes it difficult for organizers and participants to obtain schedule data quickly and accurately. Based on these issues, this research aims to design and build a web-based basketball match schedule information system that is easily accessible to all parties involved, including organizers, participants, and the general public. This system is expected to make match schedule management more efficient, structured, and transparent. The research methodology included direct observation of the schedule management process, interviews with organizers, literature review related to sports information systems, and system development using the Waterfall model. This model encompasses the stages of systems engineering, requirements analysis, system design, coding, testing, and maintenance. The system was built using the PHP programming language and a MySQL database, enabling it to store, manage, and display match schedule information in real time. The system can be accessed through any internet-connected device, such as a computer, laptop, or smartphone. The research results are a web-based application that facilitates organizers in managing match schedules effectively and minimizes the risk of misinformation. Furthermore, this research is expected to contribute to the development of information systems in the field of sports, particularly basketball, and serve as a reference for similar research in the future.